Smart Cities Governance: Lessons Learnt from Amsterdam - Rasha ALABDALI (Communications of International Proceedings, 2020)
The adoption of the Smart City (SC) concept has been evolving with the growing need to utilize the technological advancements for serving communities and people and provide better services and solutions for their daily needs and problems. Many implementations of this concept, SC, have been taking place around the world, yet handling such a multi-disciplinary domain which requires huge engagement of stakeholders from various areas with different needs and expectations is not an easy job, as we are looking at it from a city level. Ruhlant mentions in his study that “city governance is enormously complex with the multi-faceted and multi-level ecosystem of various agencies and stakeholder groups (e.g. local governments, citizens, urban planners) that are often driven by conflicting interests” (Ruhlant, 2018).  Thus, the need to have a model or an approach to govern the interactions and engagement of all stakeholders within this context becomes very essential. The purpose of this paper is to look at the governance mechanisms used by the city of Amsterdam to draw a better understanding of how a successful smart city governs its projects.
Keywords: Smart Cities; Governance; Model; Amsterdam.